2018
DOI: 10.17219/acem/69134
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two models of inflammatory bowel disease in rats

Abstract: The experimental DSSor TNBS-induced bowel inflammation used in this study corresponds to human IBD and is reproducible with characteristics indicative of acute inflammation in the case of the protocols mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…The literature data and our study showed that in terms of morphology and histopathology, the TNBS model of colon inflammation used in the present study is adequate for early stage of Crohn's disease (CD) in humans [18,28], data not published]. The rectal administration of trinitrobenzene sulfonic acid (TNBS) results in a strictly localized trans-wall inflammation causing local immune response with dense lymphocyte infiltration and secretion of proinflammatory cytokines in the whole wall of the large intestine [29,30]. The occurrence of typical for CD features in the large intestine of rats included in our experiment was confirmed by histological analysis of the pathologically altered sections of the large intestine (rectum) and the analysis of the concentration of proinflammatory cytokines performed on the same material.…”
Section: Discussionmentioning
confidence: 92%
“…The literature data and our study showed that in terms of morphology and histopathology, the TNBS model of colon inflammation used in the present study is adequate for early stage of Crohn's disease (CD) in humans [18,28], data not published]. The rectal administration of trinitrobenzene sulfonic acid (TNBS) results in a strictly localized trans-wall inflammation causing local immune response with dense lymphocyte infiltration and secretion of proinflammatory cytokines in the whole wall of the large intestine [29,30]. The occurrence of typical for CD features in the large intestine of rats included in our experiment was confirmed by histological analysis of the pathologically altered sections of the large intestine (rectum) and the analysis of the concentration of proinflammatory cytokines performed on the same material.…”
Section: Discussionmentioning
confidence: 92%
“…The use of the TNBS-induced colitis model allowed assessing immunological parameters at various stages of development of inflammatory lesions in the colon of rats, which corresponded to CD phases characterized by different severity levels in humans. Colitis induced by rectal administration of an ethanolic solution of TNBS, which is well described in the literature [ 19 , 20 ], causes transmural changes with clinical symptoms and a histological presentation characteristic of CD in humans [ 21 , 22 ]. This colitis model is also suitable for studying cell signaling pathways [ 23 ] and for analyzing a wide spectrum of cytokines [ 21 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three days after TNBS administration, rats fed the feed without oat beta-glucan supplementation developed local acute inflammation, which is a characteristic of the active phase of CD [ 23 ]. Histological evaluation of the colon confirmed extensive transmural inflammation, including inflammation of the mucosa and submucosal layers, which are characteristics of CD [ 22 ]. Seven days after TNBS administration, these symptoms improved, indicating the onset of inflammatory remission.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the effect of oat beta-glucans on experimentally TNBS-induced colitis, which is a well-described intestinal inflammation model with predominantly Crohn’s disease-like features due to the transmural character of the inflammation. Intrarectal administration of TNBS dissolved in 50% ethanol results in the induction of colitis, which mimics human Crohn’s disease (CD) [12,13]. Ethanol disrupts the colon epithelial barrier, enabling the interaction of TNBS with colon’s tissue proteins, which cause transmural inflammation.…”
Section: Discussionmentioning
confidence: 99%